Methodological substantiation of the professional functions of Responsible persons of pharmaceutical and hospital institutions - N. O. Vetiutneva; S. H. Ubohov; L. O. Fedorova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of the work is the content analysis and methodological justification of the professional functions of the Responsible persons for quality assurance of medicines in pharmaceutical and hospital institutions. Materials and methods. The following research methods were used: system and comparative analysis, generalization, systematization, graphic modeling, observation. Research materials: normative legal acts, normative documents, recommendations of international organizations, information of wholesale and retail pharmaceutical companies, pharmaceutical and hospital institutions, professional non-governmental organizations, placed on official web-sites and collected in the process of direct observation.